Analysis of Legal Protection of Child Abducted Victims by Educators in South Lampung - Andi Setiawan (IHSA Institute, 2019)
The crime of kidnapping a child is an improper act carried out by an educator. Moreover, school is an educational institution that is very much needed for child development in the future, every child who is a victim of abduction will usually experience a negative impact on his mental development as in the case of South Lampung. The problem in this study is how is the legal protection of children abducted by educators? What are the inhibiting factors for legal protection for child victims of abduction by educators? The approach to the problem used in this study is a normative juridical and empirical juridical approach. Source and type of data consists of primary data and secondary data. The procedure for collecting data is obtained by means of library research and field studies conducted by direct interviews with respondents. After the data is collected, it is then analyzed qualitatively which is then taken as a conclusion. Based on the results of the research and discussion, it was found that legal protection for children who were abducted by educators In South Lampung, through Community Based Integrated Child Protection (PATBM), socializing children's rights, through Child Advocacy Institutions, and the Police as an effort to prevent and prevent factors that cause a person to commit a crime kidnapping children is a factor in deviant behavior (revenge), which is right because of the lack of obedience in carrying out religious orders, lack of understanding of the values ??of the faith in the perpetrator, as well as the low level of education and knowledge within the perpetrator. The inhibiting factors for legal protection for child victims of abduction by educators are the size of the community's legal awareness and the poor legal culture in the community. This can be seen from the actions of the community that are not cooperative towards investigators and lack of legal compliance. Repressive (preventive) and preventive (prevention) legal protection involves law enforcement officials, namely the Police, Child Protection Institutions, Prosecutors and Courts.Legal Protection